High‐Throughput Electron Diffraction Reveals a Hidden Novel Metal–Organic Framework for Electrocatalysis. (7th April 2021) - Ge, Meng; Wang, Yanzhi; Carraro, Francesco; Liang, Weibin; Roostaeinia, Morteza; Siahrostami, Samira; Proserpio, Davide M.; Doonan, Christian; Falcaro, Paolo; Zheng, Haoquan; Zou, Xiaodong; Huang, Zhehao
Abstract: Metal‐organic frameworks (MOFs) are known for their versatile combination of inorganic building units and organic linkers, which offers immense opportunities in a wide range of applications. However, many MOFs are typically synthesized as multiphasic polycrystalline powders, which are challenging for studies by X‐ray diffraction. Therefore, developing new structural characterization techniques is highly desired in order to accelerate discoveries of new materials. Here, we report a high‐throughput approach for structural analysis of MOF nano‐ and sub‐microcrystals by three‐dimensional electron diffraction (3DED). A new zeolitic‐imidazolate framework (ZIF), denoted ZIF‐EC1, was first discovered in a trace amount during the study of a known ZIF‐CO3 ‐1 material by 3DED. The structures of both ZIFs were solved and refined using 3DED data. ZIF‐EC1 has a dense 3D framework structure, which is built by linking mono‐ and bi‐nuclear Zn clusters and 2‐methylimidazolates (mIm − ). With a composition of Zn3 (mIm)5 (OH), ZIF‐EC1 exhibits high N and Zn densities. We show that the N‐doped carbon material derived from ZIF‐EC1 is a promising electrocatalyst for oxygen reduction reaction (ORR). The discovery of this new MOF and its conversion to an efficient electrocatalyst highlights the power of 3DED in developing new materials and their applications. Abstract : Three‐dimensional electron diffraction can be used as a high‐throughput technique for discovering new materials, such as metal–organic frameworks, especially when they are synthesized in a phase mixture.